Properties of tyre dust-filled low density polyethylene composites: The effect of phthalic anhydride - Supri, Ghani, Prof. Madya; Yow, Zheng Feng; Hanafi, Ismail, Prof. (Taylor and Francis Group, LLC., 2013)
Link to publisher's homepage at http://www.tandfonline.com/